THE ROLE OF EMERGENCY NURSING IN NEW NORMAL ADAPTATION: A NARRATIVE REVIEW - Dini Prastyo Wijayanti; Meli Diana; Dimas Hadi Prayoga (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
The new normal for nurses is a push to revitalize the profession, especially for emergency nurses. Many patients with COVID-19 will be asymptomatic or minimally symptomatic. The role of Emergency Nurses as frontline in Pandemic have to adaptation with new standard for guideline personal protection equipment. The purpose of this study was to discuss the role of Emergency Nursing in in new normal adaptation during pandemic of Covid-19. This is a theoretical reflection based on the scientific literature. The pandemic emphasizes the importance of nursing care for the preservation of life and the right to health, and the Nursing Now Campaign echoes the demand for recognition of nursing practitioners who are at the frontline fighting of the COVID-19. Nursing practitioners have vital role as care giver, educator, advocacy, researcher and agent of change. Emergency of nursing have vital role in new normal adaptation as frontline. Nursing must consider its own worth, expand its potential for lifelong learning role as care giver, educator, advocacy and researcher, and be mindful be agent of change.